An early combination of concurrent chemoradiotherapy with immune checkpoint inhibitors for cervical cancer is superior to a late combination: a propensity-score matching analysis - Ma, Yi-Ming; Cheng, Shu-Xia; Zhang, Ming-Chuan; Zhang, Hui-Ying; Gu, Jun-Jiao; Zhao, Pan-Pan; Ge, Hong (Frontiers in Oncology, 2024)
PurposeThis study compared the timing effects of immune checkpoint inhibitor (ICIs) administration on the efficacy and safety of concurrent chemoradiotherapy for cervical cancer.MethodsThis study included patients with advanced cervical cancer who received concurrent chemoradiotherapy with ICIs. The patients were divided into early-application (n=51) and late-application groups (n=56) according to the ICI application timing. The primary objective was assessing progression-free survival (PFS) and its associated factors; secondary objectives included assessing objective remission rates (ORR) and treatment-related adverse events (TRAEs).ResultsBefore propensity score matching (PSM), the median PFS (mPFS) times were significantly different: 11.5 months (95% CI: 11.0–13.2) and 7.5 months (95% CI: 6.5–9.0) for the early and late groups, respectively (P<0.001). After PSM, the mPFS times remained significantly different: 11.5 months (95% CI: 11.0–13.8) and 6.5 months (95% CI: 6.1–9.0), respectively (P<0.001). The PSM tumor-response ORR in the early combination group (74.3%) was significantly greater than the 31.4% in the late combination group (P<0.001). After PSM, multivariate Cox analysis showed tumor diameter (P=0.004), distant organ metastasis (P=0.047), and timing of combination therapy (P<0.001) were independently associated factors affecting PFS. The most common TRAEs in the two groups of patients were neutropenia, nausea and vomiting, and fatigue, with no significant difference in incidence (P>0.050).All adverse reactions were resolved, and no adverse reaction-related deaths occurred.ConclusionIn patients with cervical cancer treated with concurrent chemoradiotherapy, earlier immunotherapy improves survival and is equivalent in safety to ICIs late application.